2005
DOI: 10.1253/circj.69.654
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Acute-Phase Endothelin-1 in Acute Myocardial Infarction Patients Treated With Direct Coronary Angioplasty

Abstract: ndothelins (ET) are 21-amino-acid peptides produced by the endothelium and which play important roles in cardiovascular physiology and pathophysiology. 1 The most important ET produced by the endothelium is ET-1, which has an important role in the vasoconstriction of the peripheral arterial system and also of the coronary vascular bed. 2 Elevated plasma concentrations of ET have been observed in patients suffering from diverse cardiovascular diseases, such as congestive heart failure, 3-5 pulmonary hypertensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 32 publications
0
25
0
2
Order By: Relevance
“…We have also previously shown that females have a significantly higher mortality. 25) By multivariate analysis, however, female gender was not an independent predictor of cardiac mortality. Therefore, we concluded the gender difference between smokers and nonsmokers in this study did not influence survival advantage.…”
Section: Discussionmentioning
confidence: 89%
“…We have also previously shown that females have a significantly higher mortality. 25) By multivariate analysis, however, female gender was not an independent predictor of cardiac mortality. Therefore, we concluded the gender difference between smokers and nonsmokers in this study did not influence survival advantage.…”
Section: Discussionmentioning
confidence: 89%
“…In acute myocardial infarction, endothelin-1 levels are increased but are not correlated with HANP levels [17]. BNP acts as an emergency hormone that assists atrial natriuretic peptide(ANP) to regulate blood pressure and body fl uid volume.…”
Section: Discussionmentioning
confidence: 99%
“…23 Comparison with the BNP assay suggests that NT-proBNP could play an additional role in the evaluation of patients with LV systolic dysfunction. 18 The number of patients for whom inotropic agents were required was significantly lower in the group with the low NT-proBNP level than in the group with the high NTproBNP level (p<0.05). The mean duration of inotropic agent usage was 0.46±1.13 h in Group A and 5.92±6.40 h in Group B.…”
Section: Discussionmentioning
confidence: 86%
“…NT-proBNP levels are reported to be significantly related to LVEF values and increased in patients with LV dysfunction. 18 Plasma NTproBNP is a useful marker for recovery after a high-risk CABG procedure, and conversely significantly correlated with LVEF, and it increases as the LVEF declines. 19,20 In our study we found the LVEF value was statistically significantly higher in Group A than in Group B.…”
Section: Discussionmentioning
confidence: 98%